We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
320
1
avatar+122 

The equation of a circle is (x - h)^2 + (y - k)^2 = r^2

(x  - 0)^2 + (y - 0)^2 = 1^2

x^2 + y^2 = 2

(where is my mistake?)

 Mar 31, 2018
 #1
avatar+8394 
+3

1^2   =   1 * 1   =   1

 

Does that help?  smiley

 Mar 31, 2018

7 Online Users

avatar
avatar